HLA-DQ beta-chain restriction fragment length polymorphism as a risk marker in type 1 (insulin-dependent) diabetes mellitus: a Finnish family study - Reijonen, H; Ilonen, J; Knip, M; Michelsen, B; Akerblom, H K (Diabetologia, 1990)
Finnish Type 1 (insulin-dependent) diabetic families were analysed for HLA-DQ beta-chain polymorphism using a short intron-specific probe. A simple hybridization pattern was obtained in which all fragments were associated significantly with Type 1 diabetes. The simultaneous presence of two different risk markers, the allelic 12-kilobase and 4-kilobase fragments were strongly associated with Type 1 diabetes since 50% of the patients had this combination compared with only 2% of the control subjects. The cosegregated 7.5/3.0 kilobase fragments, which were associated with HLA-DR2 and DRw6 were not detected among the diabetic patients but were present in 48% of the control subjects. Our results provide further support for the location of susceptibility determining factors in the HLA-DQ gene area. The clear-cut, simple restriction fragment length polymorphism pattern obtained here, which bears a resemblance to a two allelic system, therefore makes this method applicable for estimating the risk of Type 1 diabetes at the population level.